Microbiology in the food industry электронный курс - Чернова, А. П. химик доцент Томского политехнического университета, кандидат химических наук 1984- (TPU Moodle, 2022)
The program is aimed at training specialists with competencies in the field of working with strains of microorganisms, the biotechnological process of obtaining a target food product by microbial synthesis; isolation and purification of food, and food quality control. The aim of the program: the formation of professional competencies that ensure the performance of labor functions defined by the educational standard "Specialist in the technical control of product quality" and "Specialist in the field of food biotechnology"; the development of the ability to organize activities in the field of biotechnological process to obtain food products as a result of microbial synthesis or biotransformation of the substrate; the development of the ability to control of the intermediate and / or the target product of microbial synthesis, the development of the skills to samle preparation and test foodstuffs. A distinctive feature of this program is its practical orientation with the possibility of studying and applying in practice in biotechnological laboratories of food enterprises in accordance with the subject of the program. The program is aimed not only at studying laws, Government decrees, orders of Ministries, current requirements, and methods, but also at organizing the biotechnological process of obtaining a food product, its isolation, purification, and standardization.